Konsituatīvi saistīti izteikumi reklāmas izdevumos - Rudzone, Vizbulīte (Latvijas Universitāte, 2011)
Bakalaura darba tēma ir „Konsituatīvi saistīti izteikumi reklāmas izdevumos”. Darba mērķis ir izpētīt konsituatīvi saistītu izteikumu tipus, raksturot konteksta un situācijas lomu to izveidē mūsdienu latviešu valodā un identificēt konsituatīvi saistītu izteikumu galvenos tipus jaunos reklāmas izdevumos. Bakalaura darbā izmantotais valodas materiāls ir ekscerpēts no bezmaksas reklāmas izdevumiem. Darba teorētiskajā daļā apskatītas galvenās reklāmas valodas īpatnības (1. nodaļa) un izteikumu klasifikācija (2. nodaļa) mūsdienu latviešu valodā. Bakalaura darba praktiskajā daļā analizēti ekscerpētie konsituatīvi saistītie izteikumi (3. nodaļa) un apskatīti teikumu komunikatīvie tipi (4. nodaļa) reklāmas izdevumos. Atslēgvārdi: konsituatīvi saistīts izteikums, reklāma, reducējums, parcelāts, nosaucējvienība.

The topic of the bachelor`s thesis is “Contextually and Situationally Bound Utterances in Advertising Publications”. The aim of the thesis is to explore the types of contextually and situationally bound utterances, to characterize the role of context and situation in the formation of these utterances in Modern Latvian and to identify the main types of contextually and situationally bound utterances in recent advertising publications. The material of the bachelor`s thesis consists of utterances excerpted from free advertising publications. In the theoretical part of the thesis the most important aspects of advertising language (chapter 1) and the classification of utterances in Modern Latvian (chapter 2) are described. The practical part of the bachelor's thesis contains the analysis of contextually and situationally bound utterances (chapter 3) and communicative types of sentences (chapter 4) in advertising publications. Key words: contextually and situationally bound utterance, advertisement, reduced utterance, parcelate, nominative utterance.
Contextually and Situationally Bound Utterances in Advertising Publications
Keywords: Filoloģija